Key determinants of attitudes towards Islamic banks: An exploratory study among Islamic university students - Nur Hidayati; Hafid Aditya Pradesa; Iin Agustina (Journal of Enterprise and Development (JED), 2024)
Purpose — The study seeks to identify the factors that have the greatest impact on attitudes towards Islamic banks, including awareness and knowledge of Islamic banking, adherence to Sharia principles, and collectivist or individualist attributes.Method — This study utilized quantitative methods, and the research instruments were carefully designed to measure the latent variables under investigation. The sample included 100 students from private Islamic universities in Malang City, East Java, Indonesia. Data analysis involved confirmatory factor analysis and multiple regression analysis.Result — This research highlights the crucial role of awareness and knowledge in fostering positive attitudes towards Islamic banks. Interestingly, compliance with Sharia principles was not found to significantly influence attitudes toward Islamic banks.Contribution — This research underscores the pivotal role of awareness and knowledge in fostering positive attitudes toward Islamic banks.